Factors associated with obstetric fistula among reproductive age women in Ethiopia: a community based case control study - Ataklti Gebretsadik Woldegebriel; Gebremedhin Gebreegziabiher Gebrehiwot; Abraham Aregay Desta; Kiros Fenta Ajemu; Asfawosen Aregay Berhe; Tewolde Wubayehu Woldearegay; Kiros Demoz Ghebremedhin; Nega Mamo Bezabih (BMC, 2023)
Abstract Background Obstetric fistula is a major public health concerns in Ethiopia. It is the most devastating cause of all maternal morbidities. Method Data from the 2016 Ethiopian Demographic Health Survey (EDHS) was analyzed. A community-based unmatched case control study was conducted. Seventy cases and 210 non cases were selected using random number table. Data were analyzed by using STATA statistical software version 14. Multivariable logistic regression model was applied to determine the factors associated with fistula. Results The majority of fistula cases were from rural residences. The multivariable statistical model showed that rural residence (Adjusted OR (AOR) = 5, 95% CI 4.26, 7.52), age at first marriage (AOR = 3.3, 95% CI 2.83, 4.60), poorest wealth index (AOR = 3.3, 95% CI 2.24, 5.01) and decision making for contraceptive use by husband alone (AOR = 1.3, 95% CI 1.124, 1.67) were factors significantly associated with obstetric fistula. Conclusion Age at first marriage, rural residence, poorest wealth index and decision making for contraceptive use by husband alone were significantly associated factors for obstetric fistula. Intervening on these factors will reduce the magnitude of obstetrics fistula. In this context there is in-need to improve on avoiding early marriage through awareness creation to the community and developing legal framework by the policymakers. Furthermore, information about the joint decision making to use contraceptives should be disseminated though mass-media and interpersonal channels.